New Trajectories of Quranic Studies in Indonesia: A Critical Dissertation Review - Rohman, Nur; Hamdi Putra Ahmad (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This study aims to see the study of the Qur'an in Indonesia during the years 2015 to 2021 through dissertations at UIN Syarif Hidayatullah Jakarta, UIN Sunan Kalijaga Yogyakarta, UIN Alauddin Makassar, UIN Sunan Ampel Surabaya and UIN Walisongo Semarang. Historically, the five institutions have provided doctoral programs for a long time and are influential in producing Islamic knowledge in Indonesia. This study seeks to map the typology of the study, the issue being discussed, and the methodology developed. The data collection process was carried out by entering the college repository, mapping the results of existing dissertations and analyzing them. This study shows that throughout 2015-2020, there were 78 dissertations discussing various issues. While the study typology shows that the existing dissertation is dominated by 37 leaders' studies (47.43%) followed by the Study of Thematic Qur'an as many as 23 pieces (29.48%), the Ulumul Qur'an study of 10 pieces (12.82%) and the study of the Qur'an in everyday life as many as 8 pieces (10.26%). Typology of this study shows the development of methodology in the discourse of Quranic studies, although it is still dominated by the aspects of thematic Qur'anic thinking and studies.